Effect of feeding Artemisia capillaris on egg production and egg quality in quail - M. Sychov; D. Umanets; I. Balanchuk; R. Umanets; I. Ilchuk; T. Holubieva (Тваринництво та технології харчових продуктів, 2024)
The use of safe, natural feed additives in animal feeding is becoming increasingly important to provide animals with biologically active substances, reduce the risk of chemicals being transferred to the end consumer through products, their accumulation, and increase productivity. The purpose of the study was to determine the effect of Artemisia capillaris on egg productivity of quail hens. To conduct the experiment, 4 groups were established – a control group and three experimental groups, 72 animals (♀60+♂12) in each. The experiment, which lasted 210 days, involved feeding poultry with complete balanced feeds that had the same chemical composition and differed only in the content of the test additive, which was introduced into the feeds of poultry of experimental groups 2,3, and 4 in the amount of 0.5%, 1.0%, and 1.5% by weight of the feed, respectively. The introduction of dry wormwood powder in mixed feed of quail hens in the amount of 0.5-1.5% has a positive effect on such indicators of egg productivity as the gross yield of eggs, which increased in the experimental groups by 2.6-5.6%, the egg weight increased by 5.6-12.9%, while feed costs decreased by 2.8%. According to the qualitative indicators of eggs, there was an increase in the absolute weight of yolk by 3.0-8.3%, albumen by 2.6-6.5%, shell by 0.6-1.2%, and a decrease in the egg index by 0.9-4.1%. Feeding A. Capillaris to poultry leads to an increase in the content of palmitic, stearic, oleic, linolenic, eicosanoic, and arachidonic fatty acids in egg yolk by 0.01-6.07%. The optimal level of A. Capillaris in the diet was determined to be 1.0% of the total weight of the feed; this amount had a positive effect on the above indicators, increasing them, which can be used in the industrial technology of quail eggs production, and in organic production